Exogenous application of Methyl salicylate induces defence in Brassica against peach potato aphid Myzus persicae - Ali, Jamin; Wei, Dongming; Mahamood, Mohammad; Zhou, Fanrui; King, Patricia Jie Hung; Zhou, Wenwu; Shamsi, Imran Haider (Multidisciplinary Digital Publishing Institute, 2023)
Plants use a variety of secondary metabolites to defend themselves against herbivore insects. Methyl salicylate (MeSA) is a natural plant-derived compound that has been used as a plant defence elicitor and a herbivore repellent on several crop plants. The aim of this study was to investigate the effect of MeSA treatment of Brassica rapa subsp. chinensis (‘Hanakan’ pak choi) on its interactions with peach potato aphids, Myzus persicae, and their natural enemy, Diaeretiella rapae. For this, we selected two concentrations of MeSA (75 mg/L and 100 mg/L). Our results showed that aphid performance was significantly reduced on plants treated with MeSA (100 mg/L). In a cage bioassay, the MeSA (100 mg/L)-treated plants showed lower adult survival and larviposition. Similarly, the MeSA (100 mg/L)-treated plants had a significantly lower aphid settlement in a settlement bioassay. In contrast, the M. persicae aphids did not show any significant difference between the MeSA (75 mg/L)-treated and control plants. In a parasitoid foraging bioassay, the parasitoid D. rapae also did not show any significant difference in the time spent on MeSA-treated and control plants. A volatile analysis showed that the MeSA treatment induced a significant change in volatile emissions, as high numbers of volatile compounds were detected from the MeSA-treated plants. Our results showed that MeSA has potential to induce defence in Brassica against M. persicae and can be utilised in developing sustainable approaches for the management of peach potato aphids.